Environmental Communication and Climate Change: A Critical Analysis - Lubis, Hamidah Azzahra S; Nurul Amaliyah Tanjung; Vinna Dinda Kemala; Ummi Salamah Lubis (Faculty of Communication Science | Universitas Pancasila Jakarta, Indonesia, 2024)
Climate change is a global challenge that requires effective environmental communication strategies to raise public awareness, drive community engagement, and influence policy. Environmental communication is a critical tool in addressing climate change, with its effectiveness dependent on strategic media framing, inclusive public engagement, and persuasive policy communication. Case studies such as the Indonesian Mangrove Restoration Program and the Fridays for Future movement highlight the transformative potential of culturally sensitive and digitally integrated strategies. This study analyzes the role of environmental communication in addressing climate change. Using a systematic literature review approach to analyze current research on environmental communication and climate change, the study focused on publications between 2015 and 2023 to ensure relevance. Keywords such as “environmental communication,” “climate change,” “public engagement,” and “media strategy” guided the search. Findings from the study showed that A total of 50 articles were selected based on their focus on communication strategies and climate action. The data were analyzed thematically, categorizing findings into key themes such as media framing, public engagement, and policy communication